GE_GERICHTE P/747/2019 vom 12. Juli 2020 - GE Cour de justice (2020)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT;TENTATIVE(DROIT PÉNAL);INTERDICTION D'EXERCER UNE PROFESSION | CP.187.ch1; CP.22; CP.67.al3; CP.67.al4bis